Paleolimnology in the pantanal: Using lake sediments to track quaternary environmental change in the world’s largest tropical wetland - McGlue, Michael M.; Silva, Aguinaldo; Assine, Mario L. [UNESP]; Stevaux, José C. [UNESP]; Pupim, Fabiano do Nascimento (Springer Nature, 2016)
In spite of its global significance to biodiversity and biogeochemical cycles (e.g., as a methane source and carbon dioxide sink), the Pantanal of western Brazil remains underexplored from the perspective of Quaternary paleoecology, paleogeography, and paleoclimatology. Long in the scientific and cultural shadow cast by the Amazon Basin, recent research using lake sediment cores from different sites across the Pantanal lowlands has provided a glimpse at the sensitivity of this savanna floodplain wetland to climate-driven perturbations in the hydrologic cycle. Understanding the controls and feedbacks associated with this sensitivity is important, as the Pantanal is a critical freshwater resource situated in the headwaters of the immense Río de la Plata Basin. Published lake sediment archives have adopted a multi-indicator analytical approach, focusing on physical sedimentology, geochemistry, palynology, and siliceous microfossils. Such studies extend in time from the late Pleistocene to the present day, with the greatest emphasis placed on reconstruction of the Holocene environmental history. Several important transitions in effective precipitation have been inferred for the Holocene, which appear to be dominantly linked to variability in insolation and the South American Summer Monsoon system. By contrast, evidence of aridity in the Pantanal during the Last Glacial Maximum suggests that the wetlands also respond in a complex manner to Northern Hemisphere ice volume and that insolation forcing alone fails to fully explain patterns of environmental change. The great diversity of lacustrine ecosystems in the Pantanal warrant additional study and hold the potential to broaden our understanding of the response of tropical wetlands to global change. Such insights will be valuable for conservation planning, resource security, and sustainable management.
Keywords: Brazil; Lakes; Sediment cores; Tropical paleoclimatology; Wetlands